Documentation collections for the study of women: the archive of the Foral community administration - Sola Landa, María Teresa (Huarte de San Juan. Geografía e Historia, 2020)
The Administration Archive custodies a set of documentary funds those are essential for the study and research of the female world. Through the files deposited in the Archive, the presence of women and their evolution can be verified from areas related to home and family to their massive incorporation in to the labour market. «Women and documents» is a dissemination project carried out by the Archive whose main objective is to publicize those documents that attest to the social function of women in Navarra from the 40s of the xxth century to the present while opening new lines of investigation.